Pengaruh Analisis Jabatan Terhadap Kinerja Pada Guru dan Staf Honorer SMK Pertiwi Sukamandi - Putri Munggarani Rahayu; Banuara Nadeak; Didit Supriyadi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
Job Analysis is a formal organizational document containing a summary of important information about a position to make it easier to distinguish one position from another in an organization. The job analysis is arranged in a structured format so that the information is easily understood by all parties involved in an organization. In essence, job analysis is a basic raw material in HR management in an organization, where a position is explained and given boundaries. This study aims to find out job analysis (X) has a significant effect on performance (Y) at SMK Pertiwi Sukamandi which takes a population of teachers and staff of 107 respondents. While the method of data collection method used is to use a questionnaire (Survey) on all teachers and staff of SMK Pertiwi Sukamandi. The methods used to process and analyze the data are validity test, reliability test, simple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of the study show that job analysis has a positive effect on performance, it can be interpreted that the proposed hypothesis is accepted.